Point defects in crystals of charged colloids - Alkemade, Rinske M.; de Jager, Marjolein; van der Meer, Berend; Smallenburg, Frank; Filion, Laura (American Institute of Physics, 2021)
Charged colloidal particles—on both the nano and micron scales—have been instrumental in enhancing our understanding of both atomic and colloidal crystals. These systems can be straightforwardly realized in the lab and tuned to self-assemble into body-centered-cubic (BCC) and face-centered-cubic (FCC) crystals. While these crystals will always exhibit a finite number of point defects, including vacancies and interstitials—which can dramatically impact their material properties—their existence is usually ignored in scientific studies. Here, we use computer simulations and free-energy calculations to characterize vacancies and interstitials in FCC and BCC crystals of point-Yukawa particles. We show that, in the BCC phase, defects are surprisingly more common than in the FCC phase, and the interstitials manifest as so-called crowdions: an exotic one-dimensional defect proposed to exist in atomic BCC crystals. Our results open the door to directly observe these elusive defects in the lab.
Keywords: Taverne; General Physics and Astronomy; Physical and Theoretical Chemistry